Microcontroller-driven hydrogen car - Queirós, Hugo (2006)
This paper presents a hydrogen-powered car with 8 minutes autonomy. The hydrogen is produced by electrolysis, which requires an external power supply. The gas is retained on an isolated compartment in the car. Then, it goes to the fuel cell, which produces the energy for the car motor. The car follows a white line on a black track using five infrared sensors that detect white and black colors. A servomotor controls its direction. Guidelines to the servomotor are given by a system based on an 8051 microcontroller, according to the information it receives from the infrared sensors.